Cone-beam computed tomography–guided precise chemoembolization for hypovascular hepatocellular carcinoma - Sun, Chengzi Jun; Zhou, Jiahui (Vojnosanitetski pregled, 2026)
Background/Aim. Hypovascular hepatocellular carcinoma (HCC) remains a therapeutic challenge owing to its inadequate arterial supply and limited responsiveness to standard transarterial chemoembolization (TACE). The aim of this study was to assess the clinical efficacy and safety of cone-beam computed tomography (CBCT) three-dimensional (3D) imaging-guided precise TACE vs. conventional digital subtraction angiography (DSA)-guided TACE in the treatment of hypovascular HCC. Methods. A retrospective study was performed on patients with hypovascular HCC who underwent TACE at our institution from January 2020 to December 2023. Using propensity score matching (PSM) with a 1 : 1 ratio, 58 patients were allocated to each of the two groups: the CBCT-guided precise TACE group (CBCT group) and the conventional DSA-guided TACE group (DSA group). Matching covariates included age, gender, Child-Pugh grade, tumor size, and tumor number. Short-term efficacy, long-term survival, and safety profiles were compared between the two groups. Results. Three months after the procedure, the CBCT group exhibited a markedly higher objective response rate (63.79% vs. 36.21%) and disease control rate (86.21% vs. 68.97%) compared to the DSA group (p < 0.05). Regarding long-term survival, the CBCT group exhibited significantly prolonged median progression-free survival (10.80 months vs. 7.10 months) and a higher 1-year progression-free survival rate (65.52% vs. 41.38%) compared to the DSA group (p < 0.05). However, no statistically significant differences were observed between the CBCT and DSA groups for median overall survival (22.50 months vs. 19.10 months) or the 1-year overall survival rate (81.03% vs. 72.41%) (p > 0.05). The incidence of post-embolization syndrome and severe complications (e.g., liver abscess, hepatic failure) did not differ significantly across the groups (p > 0.05). Notably, the elevation in alanine aminotransferase levels on the third postoperative day was considerably lower in the CBCT group than in the DSA group (p = 0.016). Conclusion. CBCT 3D imaging-guided precise TACE significantly enhances short-term therapeutic efficacy, prolongs progression-free survival, and provides superior hepatoprotection without increasing procedural risks, establishing it as a safe and effective interventional treatment option for hypovascular HCC.
Keywords: angiography, digital subtraction; carcinoma, hepatocellular; chemoembolization, therapeutic; cone-beam computed tomography; imaging, three-dimensional; treatment outcome.